Switzerland : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This Selected Issues paper takes a close look at the proximate determinants and short-term dynamics of inflation in Switzerland. It identifies salient features of the inflation experience in Switzerland. The paper uses a wage-price model to gauge the sensitivity of inflation to the business cycle and the exchange rate. The findings suggest that underlying inflation of about 1 percent reflects a slightly higher rate for domestic goods and services and low increases in prices of imported goods.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet